Burgeoning therapeutic strategies to curb the contemporary surging viral infections. (June 2023) - Akram, Fatima; Waheed, Hafiza Marium; Shah, Fatima Iftikhar; Haq, Ikram ul; Nasir, Narmeen; Akhtar, Muhammad Tayyab; Farooq Gohar, Umar
Abstract: Significant efforts and initiatives were already made in the health care systems, however in the last few years; our world is facing emergences of viral infections which potentially leading to considerable challenges in terms of higher morbidity, mortality, increased and considerable financial loads on the affected populations. Over ten major epidemics or pandemics have been recorded in the twenty-first century, the ongoing coronavirus pandemic being one of them. Viruses being distinct obligate pathogens largely dependent on living beings are considered as one of the prominent causes of death globally. Although effective vaccines and antivirals have led to the eradication of imperative viral pathogens, the emergences of new viral infections as well as novel drug-resistant strains have necessitated the implementation of ingenious and efficient therapeutic approaches to treat viral outbreaks in the future. Nature being a constant source of tremendous therapeutical resources has inspired us to develop multi-target antiviral drugs, overcoming the challenges and limitations faced by pharmaceutical industry. Recent breakthroughs in the understanding of the cellular and molecular mechanisms of viral reproduction have laid the groundwork for potential treatment approaches including antiviral gene therapy relying on the application of precisely engineered nucleic acids for disabling pathogen replication. The development of RNA interference and advancements in genome manipulating tools have proven to be especially significant in this regard. In this review, we discussed mode of actions and pathophysiological events associated with the viral infections; followed by distributions, and advancement made towards the detection strategies for timely diagnosis. In the later section, current approaches to cope up the viral pathogens and their key limitations have also been elaborated. Lastly, we also explored some novel and potential targets to treat such infections, where attentions were made on next generation gene editing technologies. Graphical abstract: Image 1 Highlights: Viruses are the cause of potential pandemics in 21st century. Perception of viral infection can help in devising the therapeutic approaches. Current approaches for targeting are entry, fusion, integration, and elimination. Use of natural elements against viral infection may be an emerging therapeutic strategy. CRISPR, RNAi, and ZFNs are new therapeutic trends for viral treatment.